2014
DOI: 10.4103/1947-2714.128474
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of temporomandibular disorder in children and adolescents from public schools in Southern Portugal

Abstract: Background:The prevalence of temporomandibular disorder (TMD) in children and adolescents is in the range of 6-68% and can be triggered or aggravated by emotional stress.Aim:The study was to investigate the prevalence of TMD in Portuguese children and adolescents and its association with emotional stress.Materials and Methods:The sample comprised 3,260 students aged 5-19 years. The questionnaire was used to assess the presence of TMD, and was applied in a single moment.Results:TMD was observed in 821 (25.2%) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
1
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 24 publications
(45 reference statements)
2
36
1
5
Order By: Relevance
“…This is in consistent with others studies [1,15,27,29,30], and inconsistent with others reports (slightly lower than our results) [10,16,24,31,32], In contrast , some studies reported a higher rate of signs and symptoms of TMDs in compared to our fi nding [22,[32][33][34].…”
Section: Discussioncontrasting
confidence: 54%
See 3 more Smart Citations
“…This is in consistent with others studies [1,15,27,29,30], and inconsistent with others reports (slightly lower than our results) [10,16,24,31,32], In contrast , some studies reported a higher rate of signs and symptoms of TMDs in compared to our fi nding [22,[32][33][34].…”
Section: Discussioncontrasting
confidence: 54%
“…Free of any symptoms TMDs, 20.77 (n =43) had, mild TMD dysfunction (11.11 % were females and 9.66% were males), 12.08 (n= 25) had a moderate TMD dysfunction (7.73% were females and 4.35 were males) and 16.91 % (n = 35) had a severe TMD dysfunction (10.63% were females and 6.28 % were males). A 50.24% (n= 104) were a free of symptoms.…”
Section: Ai0mentioning
confidence: 99%
See 2 more Smart Citations
“…In most studies that employed a questionnaire [13][14][15][16], surveys of awake clenching were based on self-reports, and most patients were instructed by dentists to "take care to avoid clenching" and that "you should not be clenching." However, patients may be unaware of the magnitude of bite force that is equivalent to clenching; therefore, they may not be able to follow the advice of the dentist, which may adversely affect the clinical course.…”
Section: Introductionmentioning
confidence: 99%